Geochemical monitoring of subaqueous systems (theoretical and applied aspects) - Lukashev, Oleg V.; Zhukovskaya, Natallia V.; Lukasheva, Natallia G.; Savchenko, Vladimir V. (Journal of the Belarusian State University. Geography and Geology, 2017)
The article has considered some general patterns of the trace elements migration and concentration in the hydrosphere and their removal in the lithosphere with sedimentation. Technological and geochemical features of trace elements accumulation in sediments have been studied by example of strongly expressed geochemical environment (city on a small river). The author has shown the effectiveness and limitations in applying the method of chemical elements normalization on Fe in the river bottom sediments. The fraction increase of trace elements mobile forms in the bottom sediments of a river type reservoir has been determined. The author has revealed natural and anthropogenic trace elements associations in the bottom sediments by using multivariate statistical analysis.
Keywords: bottom sediment; chemical elements; geochemical monitoring; technogenic contamination; concentration coefficient; chemical elements associations